Financial markets : the accumulation and allocation of wealth - Robinson, Roland I.; Wrightsman, Dwayne (New York : McGraw-Hill, 1980)
A high school textbook introducing the basic principles of money and capital markets.
Includes bibliographies and index.
Keywords: Finance -- United States; Money market -- United States; Capital market -- United States; Finance; Money market; Capital market